The End of Love? Questioning Technocracy in Plato’s Symposium - Krinks, Philip (Revista Archai, 2020)
Plato’s Symposium contains two accounts of eros which explicitly aim to reach a telos. The first is the technocratic account of the doctor Eryximachus, who seeks an exhaustive account of eros, common to all things with a physical nature. For him medical techne can create an orderly erotic harmony; while religion is defined as the curing of disorderly eros. Against this Socrates recounts the priestess Diotima finding a telos, not in technical exhaustiveness, but in a dialectical definition of eros in the light of the good. What is common to all human beings is the desire to be in eternal relation to the good. All technai are forms of poiesis, by which things pass from being to not being. The erotic harmony recommended by Eryximachus, no less than the Aristophanes” recommendation of eros as “of a half, or of a whole’, is subject to the question whether “it happens to be good’. A self-harmonisation produced by techne can no more evade the sovereignty of good, than can projects of self-completion with a beloved in our likeness.